Penggunaan Model Pembelajaran Problem Based Learning untuk Meningkatkan Kemampuan Menyimak Siswa Kelas 1 SD Negeri Mranak 2 Tahun Ajaran Gasal 2021/2022 - Solikhin Solikhin (Perkumpulan Kualitama Edukatika Indonesia, 2022)
The aim of this research is to improve the learning outcomes of class V students at SD Negeri Mranak 2 using the PBL Learning Model for the 2021/2022 odd school year in the Indonesian language subject of listening material. This research is classroom action research (PTK) with 4 stages of implementation through cycle I and cycle II. The data collection techniques in this research are written test techniques, documentation, observation through cycle I and cycle II. Data analysis in this research is student learning outcomes in cycle I and student learning outcomes in cycle II using descriptive statistical tests. Grade 1 students at SD Negeri Mranak 2 were able to improve learning outcomes for listening material from cycle I with class classical completeness of 9 students (39.13%) and in cycle II with class classical completeness of 20 students (86.96%) with a minimum score of obtained in accordance with the minimum KKM that students must obtain, namely 75.